Censorship detected in BY (Belarus) - Voidly (Voidly Global Censorship Index, 2026)
CRITICAL severity censorship detected in Belarus. Data sourced from OONI, CensoredPlanet.
Censorship Incident ID: BY-2026-1484. Severity: critical. Confidence: 90%